Vibration mitigation performance of active tuned mass damper in a super high-rise building during multiple tropical storms. (15th October 2022) - Zhou, Kang; Li, Qiu-Sheng
Highlights: Conduct field measurements on a 600-m-tall building equipped with an active tuned mass damper (ATMD) system during seven tropical storms. Assess the ability of the ATMD system for mitigating wind-induced vibrations. Evaluate control performance of the ATMD system by investigating its effects on structural dynamic properties. Abstract: On the basis of field measurements on a super high-rise building equipped with an active tuned mass damper (ATMD) system during seven tropical storms, this paper presents a systematic investigation of the vibration mitigation performance of the active control system under extreme wind conditions. The field-measured building acceleration responses indicate that the ATMD system can be precisely triggered to operate following its operating principle and significantly suppress the acceleration responses of fundamental sway modes of the monitored skyscraper but has marginal effects on those of higher modes. Moreover, the effects of the ATMD system on structural dynamic properties of the super high-rise building are investigated. The results show that the damping ratios of the fundamental sway modes can be remarkably boosted from about 0.6 % to 2 % ∼ 7 % by the active damper system, and the increment of damping ratios decreases as building vibration amplitude. The outputs of this paper aim to offer advantageous guidance for the design of vibration control devices and thereby provide helpful information for the wind-resistant design of super high-rise buildings.